A Survey on Workplace Violence Experienced by Critical Care Physicians - Kumar, Nadikuda Sunil (Indian J Crit Care Med, 2019)
INTRODUCTION: Workplace violence (WPV) has been defined as, “violent acts including physical assault and threats of assault directed toward personnel at work or on duty”. Healthcare staff are at highest risk of WPV among the professionals and it is more common among the critical care services. Prevalence of WPV among doctors all over the world is around 56–80% and in Indian scenario, it is around 40.8–75%. There is scarcity of studies on WPV among doctors from India. To our knowledge, this is the first of its kind survey conducted to know about the incidence of WPV amongst critical care physicians in India. MATERIALS AND METHODS: This survey was conducted after taking due ethical committee clearance amongst critical care physicians attending a critical care conference. The purpose of the study was informed to the participants and a pretested, self-administered, semi-structured questionnaire was distributed among them for their voluntary and anonymous response. RESULTS: Out of 160 delegates who were given the questionnaire, 118 responses were collected and their forms were analyzed. Maximum responses (84%) received were of age group 20–40 years. Seventy-two percent respondents experienced WPV during their work hours. Most common type of violence reported was verbal violence (67%). Sixty-five percent respondents reported that poor communication was the leading cause of WPV. Due to WPV, most of the respondents (60%) had to change their place and pattern of work. Proper communication (76%) was the most common measure among multiple measures suggested by respondents for avoiding WPV. Eighty-three (98%) respondents opined that conflict management should be part of regular curriculum in medical education. CONCLUSION: Improving the communication skills amongst critical care physicians, teaching doctors about conflict management in their regular curriculum of medical education, spreading awareness in public about patient rights and taking initiatives in propagating an idea to “Fight against the diseases and not against the doctors” are the key measures to combat WPV. HOW TO CITE THIS ARTICLE: Kumar NS, Munta K, Kumar JR, Rao SM, Dnyaneshwar M, Harde Y. A Survey on Workplace Violence Experienced by Critical Care Physicians. Indian J Crit Care Med 2019;23(7):295–301.